Digital Transformation in Local Trade: A Study of Perceptions among E-Commerce Sellers and Consumers - Andania, Ana; Irmawati, Irmawati; Nasaruddin, Nasaruddin; Syam, Andi Wahyuni; Anugrahwati, Anugrahwati (International Journal of Marketing & Human Resource Research, 2025)
Digital transformation has brought significant changes to the local trade ecosystem in Indonesia, including Bone Regency. This study aims to explore the readiness of MSME sellers and consumer perceptions of empowerment features in e-commerce platforms, using a phenomenological qualitative approach. A total of 10 sellers and 10 consumers who are active on the Shopee, Tokopedia, and TikTok Shop platforms were interviewed in depth, supported by virtual observation and document analysis. The results of the study indicate that the digital readiness of sellers is influenced not only by the availability of devices and networks but also by digital literacy, innovative promotional strategies, self-learning, and support from family and community. Sellers who can adapt creatively and actively across platforms are more likely to thrive in the competitive digital market. On the consumer side, features such as promotions, free shipping, ratings, reviews, and ease of returns are key factors in empowering and building trust. A preference for local products also grows stronger when supported by a good digital reputation and responsive customer service. However, there are challenges in the form of unequal access to digital training and the need for platform policy innovations that are more friendly to local MSMEs. This study emphasizes the importance of strengthening digital literacy, cross-actor collaboration, and inclusive strategies to ensure that digital transformation is effective, inclusive, and sustainable at the local level.